HUBUNGAN MEROKOK DENGAN JUMLAH KOLONI JAMUR Candida sp. PADA KARYAWAN PRODIA BANDUNG - Ratna Debby (Meditory : The Journal of Medical Laboratory, 2022)
Smoking is one of the causes of various oral diseases that begin with changes in saliva and normal flora. The oral cavity is a part that is very easily exposed to the effects of cigarettes, it is the main place for absorption of substances resulting from cigarette combustion. The normal flora of the human oral cavity includes various types of organisms including Eubacteria, Archaea, Protozoa, Mycoplasma, and Fungi. The genus Candida is the most common causative fungus. Candida infections usually develop on mucous membranes such as the mouth and are responsible for the development of disorders such as Candidiasis in the oral cavity. This study aims to determine the effect of smoking on the growth of Candida sp. to Prodia Bandung employees. The method used in this research is an analytical survey method where the sampling is obtained randomly. Based on the results of the study, it was concluded that there was no relationship between smoking habits and the number of Candida sp. on Prodia Bandung employees. Keywords: Relationship, Smoking, Colonies, Candida sp.